Economics of Sovereign Wealth Funds - Das, Udaibir; Hoorn, Han.; Mazarei, Adnan (Washington, D.C. : International Monetary Fund, 2010)
The book covers a wide range of topics of relevance to policymakers in countries that have sovereign wealth funds (SWFs) and those that receive SWF investments. Renowned experts in the field have contributed chapters. The book is organized around four themes: (1) the role and macrofinancial linkages of SWFs, (2) institutional factors, (3) investment approaches and financial markets, and (4) the postcrisis outlook. The book also discusses the challenges facing sovereign wealth funds in the coming years, from an inside perspective on countries, including Canada, Chile, China, Norway, Russia, and New Zealand. Economics of Sovereign Wealth Funds will contribute to a further understanding of the nature, strategies and behavior of SWFs and the environment in which they operate, as their importance is likely to grow in the coming years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet